Reuse of wheat flour liquid waste for enzymatic hydrolysis to yield glucose-derived bioethanol. Issue 1 (31st December 2022) - Sari, N.K.; Purbasari, I.Y.; Anggoro, P.W.; Jamari, J.; Bayuseno, A.P.
Abstract: Wheat flour liquid waste (WF-LW) is a potential biomass that is chemically pre-treated before being enzymatically hydrolyzed to produce glucose-derived bioethanol. This study investigated the effects of pH on the pretreatment process and the subsequent hydrolysis of WF-LW in the presence of amylase (AE) and maltose enzymes (ME). In the experiment, WF-LW at varying volumes from 200 to 1000 mL was treated with 5 to 25 mL of HCl and stirred for 30 minutes and at the temperature of 40°C. Impurities were removed prior to hydrolysis. Following that, a hydrolysis with an AE of 11% w/v and ME of 9% w/v resulted in a glucose content of 24.9% v/v. Moreover, 0.859 mL of HCl was added to achieve the best results, which were then optimized using SRM (surface response methodology) at a pH of 8.85 in a WF-LW volume of 1165.69 mL. The optimization of the pH and fermentation process in the presence of amylase and maltase enzymes resulted in increased glucose production and a decrease in the LW-TW treatment volume, which was 651.426 mL. These discoveries would become an appropriate approach for the subsequent fermentation process, resulting in the highest glucose levels possible.